2011
DOI: 10.1177/039463201102400130
|View full text |Cite
|
Sign up to set email alerts
|

Search for Genomic Sequences of Microbial Agents in Atherosclerotic Plaques

Abstract: Atherosclerosis is a complex, multifactorial disease. Several studies have reported a possible association between infection with microbial agents and atherogenesis. Chlamydia pneumoniae (C. pneumoniae), Herpes Simplex Virus 1 (HSV1), Human Cytomegalovirus (HCMV), and Epstein Barr Virus (EBV) have been widely investigated for their possible role in atherosclerosis development, but the results obtained to date are contradictory. The aim of our study is to search DNA of the aforementioned infectious agents by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…C. pneumoniae also has a role in lipid accumulation in the vessel wall by upregulating lecithin-like oxidized LDL receptors (LOX-1) in both endothelial and vascular smooth muscle cells. [4344] In the same period, four studies[4548] did not find convincing evidence of presence of Chlamydophila genome in the atheromatous tissue, and argued in favor of alternative mechanisms. However, it is likely that C. pneumoniae infection may only be providing an initial trigger and is transient rather than persistent.…”
Section: Resultsmentioning
confidence: 99%
“…C. pneumoniae also has a role in lipid accumulation in the vessel wall by upregulating lecithin-like oxidized LDL receptors (LOX-1) in both endothelial and vascular smooth muscle cells. [4344] In the same period, four studies[4548] did not find convincing evidence of presence of Chlamydophila genome in the atheromatous tissue, and argued in favor of alternative mechanisms. However, it is likely that C. pneumoniae infection may only be providing an initial trigger and is transient rather than persistent.…”
Section: Resultsmentioning
confidence: 99%
“…Some trials that employed serologic methods have demonstrated a link between seropositivity to C. pneumoniae and an acute cerebrovascular accident (4-8), whereas others have not (9)(10)(11). Moreover, some studies have confi rmed the presence of C. pneumoniae in the atherosclerotic plaque by molecular genetic methods (13)(14)(15)(16)(17), but a considerable number of studies have not reported any association (18)(19)(20)(21). Likewise, the relationship between bacteria and atherosclerotic changes in intracerebral blood vessels is not straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies could not find any association between C. pneumoniae and atherosclerosis. Moreover, the studies of Tremolada et al (2011) , Bishara et al (2003) , Satpathy et al ( Satpathy, Bhan, Sharma, & Kar, 2008 ), Sodeck et al (2004) , West et al (2009) , Campbell et al ( Campell & Kuo, 2004 ), Apfalter et al (2004) , Watt et al ( Watt, Aesch, Lanotte, Tranquart, & Quentin, 2003 ) and Bossone et al (2008) did not isolate C. pneumoniae DNA from atherosclerotic specimens by PCR. Furthermore, findings of the same studies in Iran with the association between C. pneumoniae infection and atherosclerosis are contrasting, where some studies revealed an association between C. pneumoniae infection and atherosclerosis ( Rostami et al, 2013 ; Bahrmand et al, 2004 ; Dabiri et al, 2009 ) while, others could not ( Sadeghian et al, 2013 ; Zibaeenezhad et al, 2005 ; Pooria et al, 2009 ; Hosseinian, Habibzadeh, Ahari, & Mokhtarpoor, 2007 ).…”
Section: Discussionmentioning
confidence: 99%